The Role of Digital Transformation in Enhancing Corporate Social Responsibility (CSR) Initiatives: A Strategic Management Perspective (Contemporary Journal of Social Science Review, 2024)
This study explores the strategic integration of digital transformation and Corporate Social Responsibility (CSR) initiatives, focusing on how organizations can leverage digital technologies to enhance their CSR efforts. Through qualitative case studies of two multinational companies, the research examines how digital tools such as blockchain, artificial intelligence (AI), and the Internet of Things (IoT) can be strategically aligned with CSR goals to improve transparency, efficiency, and stakeholder engagement. The findings reveal that successful integration requires clear strategic alignment, investment in relevant technologies, and robust stakeholder engagement practices. The study also highlights the dual benefits of this integration, which include not only enhanced social and environmental impact but also increased innovation and competitive advantage. Implications for theory and practice are discussed, along with suggestions for future research to address the challenges and opportunities in this evolving field.